The Binding Factor for “Aging In Place”: A Literature Review - Pradipta, Amanda Nisa; Adianto, Joko (International Journal of Built Environment and Scientific Research, 2025)
This research aims to explore and synthesize the factors that bind older people to age in place. Aging in place is an alternative policy that determines older people's choice to stay in place. It is important to express this concept in a holistic approach to support the provision of age-friendly housing. A literature review was used to identify the main categories that bind older adults choosing to age in place. A total of 55 articles were reviewed to identify 18 qualified studies. The findings are five main binding factors: physical, social, economic, psychological, and autobiographical attached. The concept of aging in place is formed from the attachment of older people to their place of residence and affects their life satisfaction. And it operates at multiple scales including home, neighborhood, and broader context. Therefore, there is a need to design inclusive environments and consider emotional bonds to achieve their well-being.